Efektivitas PTSL (Pendaftaran Tanah Sistematis Lengkap) Dalam Pelayanan Administrasi Pertanahan Di Kota Batu - Putra, Langgeng Rachmatullah; Ilyas, Taufiq Rahman; Heriawanto, Benny Krestian (JPAP: Jurnal Penelitian Administrasi Publik, 2022)
Abstract:The PTSL program launched by the central government is like a breath of fresh air for the people of Batu City, where the community is greatly helped in terms of the ease of obtaining land certificates. However, in the general PTSL implementation process as regulated in PP 24 of 1997, there are several irregularities and problems, particularly related to administration which does not require a transfer deed. This study uses a qualitative approach with a SWOT analysis technique. The analysis is carried out based on maximizing strengths and opportunities, but at the same time minimizing weaknesses and threats. In conclusion, the village as the spearhead of the implementation of the PTSL program has different problems, both in terms of resources and technical aspects, namely, (1) Extension or socialization that is not comprehensive because the counseling process is carried out individually on the RT RW committee. (2) Issuance of certificates of property rights whose issuance still contains several errors. 3) There are internal problems within the Village level committee team which result in obstacles in the form of a decrease in service quality. (4) There is no certainty regarding the completion period for the issuance of the Certificate of Ownership which is announced to the public or the issuance is delayed from the schedule. Then suggestions that can be given are efforts to improve infrastructure, increase human resource capacity and be more active in conducting socialization activities both to the community and village officials, which should be carried out by the Batu City Government, in this case the Batu City Land Office.Keywords: Effectiveness, PTSL, Service, Administration Abstrak:Program PTSL yang dicanangkan oleh pemerintah pusat seperti menjadi angin segar bagi masyarakat Kota Batu, dimana masyarakat menjadi sangat terbantu dalam kaitannya kemudahan pengurusan sertifikat tanah. Namun, Pada proses penyelenggaraan PTSL secara umum sebagaimana diatur dalam PP 24 Tahun 1997 terdapat beberapa penyimpangan dan permasalahan, khususnya terkait administrasi yang tidak memerlukan adanya akta peralihan. Penelitian ini menggunakan pendekatan kualitatif dengan teknik analisis SWOT. Analisis dilakukan dengan didasarkan kepada pemaksimalan kekuatan (strength) dan peluang (opportunities), namun secara bersamaan juga meminimalkan kelemahan (weakness) dan ancaman (threats). Kesimpulan, desa sebagai ujung tombak pelakasnaan program PTSL mempunyai problem yang berbeda beda baik dari segi sumberdaya maupun teknis yakni, (1) Penyuluhan atau sosialisasi yang kurang menyeluruh dikarekan proses penyuluhan yang dilaksanakan secara individu pada panitia RT RW. (2) Penerbitan sertifikat hak milik yang penerbitannya masih terdapat beberapa kesalahan. 3) Adanya permasalahan internal dalam tim panitia tingkat Desa yang mengakibatkan adanya hambatan berupa penurunan kualitas pelayanan. (4) Tidak adanya kepastian mengenai jangka waktu penyelesaian penerbitan Sertifikat Hak Milik yang diumumkan kepada masyarakat atau penerbitan mundur dari yang sudah dijadwalkan. Kemudian saran yang dapat diberikan yakni upaya perbaikan infrastruktur, peningkatan kapasitas sumberdaya manusia dan lebih aktif dalam melakukan kegiatan sosialisasi baik kepada masyarakat maupun petugas dari pihak desa harus dilakukan oleh pemerintah kota batu dalam hal ini adalah Kantor Pertanahan kota batu.Kata Kunci: Efektivitas, PTSL, Pelayanan, Administrasi